Messina (Melilotus siculus) – a new annual pasture legume for Mediterranean-type climates with high tolerance of salinity and waterlogging - Nichols P.G.H.; Teakle N.L.; Bonython A.L.; Ballard R.A.; Charman N.; Craig A.D. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
Messina (Melilotus siculus) is a new annual pasture legume with high waterlogging tolerance and much higher salt tolerance than other legumes. Glasshouse and laboratory studies have identified several mechanisms for both salt and waterlogging tolerance that explain its adaptation to saline, waterlogged soils. Field trials are underway to select the best adapted line for release as a new cultivar. Selection is also being conducted for an adapted salt tolerant Rhizobium strain. This paper discusses the ecology, physiology and agronomy of messina and progress towards its release as a new pasture species for saline, waterlogged soils in Mediterranean-type climates.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)